Stem Cell Transplantation for Ovarian Cancer Patient with Associated Myelodysplasia After Maintenance Therapy with Olaparib: A Case Report - Linn Z; Gu Z; Wang L; Cai S (International Medical Case Reports Journal)
Zeyar Linn,1 Zhongyi Gu,1 Libing Wang,2 Shengyun Cai1 1Department of Obstetrics and Gynecology, The First Affiliated Hospital of Naval Medical University (Changhai Hospital), Naval Medical University, Shanghai, People’s Republic of China; 2Department of Hematology, The First Affiliated Hospital of Naval Medical University (Changhai Hospital), Naval Medical University, Shanghai, People’s Republic of ChinaCorrespondence: Shengyun Cai, Department of Obstetrics and Gynecology, The First Affiliated Hospital of Naval Medical University (Changhai Hospital), Naval Medical University, 168 Changhai Road, Shanghai, 200433, People’s Republic of China, Email caicai24@126.comAbstract: Ovarian cancer remains a significant cause of morbidity and mortality in women worldwide. Olaparib, a poly ADP-ribose polymerase (PARP) inhibitor, has been shown in studies to increase the time that people with cancer do not get worse. However, reports have indicated rare adverse effects, like myelodysplastic syndrome (MDS). In this report, we highlight the case of a 42-year-old female patient who was diagnosed with ovarian endometrioid carcinoma, FIGO Stage IIB. Following surgery and chemotherapy, the patient commenced maintenance therapy with Olaparib. After two years, she experienced abnormal blood test results, which ultimately led to a diagnosis of myelodysplastic syndrome (MDS), confirmed through a bone marrow biopsy. Despite initial obstacles, the patient underwent stem cell transplantation as a treatment for MDS. After undergoing stem cell transplantation, the patient experienced a notable improvement in their condition. Upon reevaluation, the transplantation proved successful as it resolved the abnormalities related to MDS. Furthermore, the ovarian cancer status showed a positive response, with no signs of disease progression during the follow-up period. This particular case emphasizes the importance of being vigilant for uncommon adverse effects, such as MDS, in ovarian cancer patients undergoing Olaparib maintenance therapy. Early diagnosis and treatment, which may include stem cell transplantation, can lead to favorable results, not only in managing MDS but also in possibly slowing down the progression of ovarian cancer that is causing it. Additional research is necessary to understand the risk factors and the most effective management approaches for these complications in this specific group of patients.Keywords: stem cell transplantation, ovarian cancer, myelodysplasia, olaparib, case report